Implementation of SIPLah as a Digitalization Tool for Procurement and Financial Management in 099 Babakan Tarogong Elementary Schools Bandung - H. Soro , Suharyanto; Wulansari, Destianti; Rusmiati, Esih (Global Education Journal, 2025)
Implementation of the School Procurement Information System (SIPLah) at SDN 099 Babakan Tarogong, Bandung, as an effort to digitize the procurement process and management of School Operational Assistance funds (OS financing limits). Education financing activities have a negative impact if they are not carried out in accordance with previously prepared planning. This study aims to find and analyze the implementation of a digital school procurement information system. Researchers used a case study approach. Data were collected through observation, interviews, and documentation. The results of the study showed that: (1) the use of SIPLah helps schools become more efficient in the procurement process, more transparent in financial management, and easier in reporting; (2) Users feel helped because the transaction process is faster and the documentation is neater, thus supporting more responsible school governance; (3) Several obstacles, such as limited digital capabilities of some school staff, technical disruptions that sometimes occur, and the still limited choice of local providers on the platform. The conclusion of this study is that the implementation of SIPLah is a step forward in realizing more modern and digital school financial management.